2006
DOI: 10.1111/j.1540-6520.2006.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Forced to Play by the Rules? Theorizing how Mixed–Sex Founding Teams Benefit Women Entrepreneurs in Male–Dominated Contexts

Abstract: We examine how establishing a mixed-sex entrepreneurial founding team may benefit women entrepreneurs in male-dominated cultures and industries. We contend that as a result of sex-based stereotypes, women entrepreneurs face unique obstacles in securing access to resources for their ventures. We argue that one way for women entrepreneurs to overcome these obstacles is to partner with a man. Drawing upon institutional, resourcebased, and network theories, we theorize how partnering with a man may help provide wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(115 citation statements)
references
References 82 publications
10
97
0
8
Order By: Relevance
“…Para eles, a formação e a educação de empresárias se apresentavam como uma alternativa consistente que poderia proporcionar a essas mulheres melhores condições não só de administrar uma empresa como também de torná-la mais competitiva. Tambunan (2007), na Indonésia, e Machado (2001) Para alguns autores, as redes contribuem positivamente para a criação e desenvolvimento de novos negócios (VALE, SERAFIM, TEODÓSIO, 2011;GODWIN, STEVENS, BRENNER, 2006;KLYVER, TERJESEN, 2007;WELTER et al, 2004). No entanto, estudos revelaram que a participação feminina em redes ainda é modesta, principalmente na fase inicial do negócio (KLYVER, TERJESEN, 2007), e que, além de elas preferirem resolver seus problemas empresariais utilizando as relações pessoais em vez da assistência das redes (WELTER et al, 2004), suas redes seriam baseadas, na maioria das vezes, na confiança (LOW, 2005 A relação entre trabalho e família, ou melhor, a busca de conciliação entre eles, também foi um tema investigado pela literatura especializada (STROBINO, TEIXEIRA, 2014;JONATHAN, SILVA, 2007;SHELTON, 2006;SILVA, 2006;LINDO et al, 2004;QUENTAL, WETZEL, 2002;UFUK, ÖZGEN, 2001).…”
Section: Almiralva Ferraz Gomes / Weslei Gusmão Piau Santana / Uajaráunclassified
“…Para eles, a formação e a educação de empresárias se apresentavam como uma alternativa consistente que poderia proporcionar a essas mulheres melhores condições não só de administrar uma empresa como também de torná-la mais competitiva. Tambunan (2007), na Indonésia, e Machado (2001) Para alguns autores, as redes contribuem positivamente para a criação e desenvolvimento de novos negócios (VALE, SERAFIM, TEODÓSIO, 2011;GODWIN, STEVENS, BRENNER, 2006;KLYVER, TERJESEN, 2007;WELTER et al, 2004). No entanto, estudos revelaram que a participação feminina em redes ainda é modesta, principalmente na fase inicial do negócio (KLYVER, TERJESEN, 2007), e que, além de elas preferirem resolver seus problemas empresariais utilizando as relações pessoais em vez da assistência das redes (WELTER et al, 2004), suas redes seriam baseadas, na maioria das vezes, na confiança (LOW, 2005 A relação entre trabalho e família, ou melhor, a busca de conciliação entre eles, também foi um tema investigado pela literatura especializada (STROBINO, TEIXEIRA, 2014;JONATHAN, SILVA, 2007;SHELTON, 2006;SILVA, 2006;LINDO et al, 2004;QUENTAL, WETZEL, 2002;UFUK, ÖZGEN, 2001).…”
Section: Almiralva Ferraz Gomes / Weslei Gusmão Piau Santana / Uajaráunclassified
“…In addition, proposed solutions stay within the status quo and do not begin to challenge gender bias in the system directly. For example, entrepreneurship scholars have recently suggested that women founders should find males to be on their teams in order to have a better chance of receiving equity funding, rather than solving the bias in the equity financing ecosystem itself (Godwin et al, 2006). These "solutions" the field provides individual women do nothing to challenge the structural bias in the entrepreneurial institutions themselves.…”
Section: New Approaches For the Study And Practice Of Entrepreneurshipmentioning
confidence: 99%
“…Although gender awareness has increasingly informed analyses of entrepreneurial behaviours since the 1990s, much of this work this has been framed comparatively (Eddleston & Powell, 2008;Godwin, Stevens, & Brenner, 2006). Embedded within this epistemology is an underlying presumption that men and women are fundamentally different and that such differences will be articulated as female deficiency.…”
Section: Revealing and Concealing Gender Within Entrepreneurial Theormentioning
confidence: 99%